Inclusive J/ψ and ψ production in p-Pb collisions at √sNN=5.02 TeV with ALICE at the LHC - Winn, Michael (Nuclear physics. A, Nuclear and hadronic physics, 2014)
We report on the inclusive J/ψJ/ψ nuclear modification factor in p-Pb collisions at sNN=5.02 TeV as a function of rapidity y and transverse momentum pTpT. The experimental coverage extends down to pT=0 GeV/cpT=0 GeV/c in the three rapidity ranges accessible by ALICE (−4.46